Pengaruh variabel kebutuhan fiskal terhadap alokasi DAU pada daerah bercirikan kepulauan - Luthfia Maha Reni; Doddy Setiawan (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2019)
This study aims to see the effect of fiscal need variables on the allocation of the General Allocation Fund (DAU) in the islanding area by three regional categories based on topography. The independent variables used were population, area, human development index, construction cost index, and GRDP. The research method used is multiple linear regression analysis and ANOVA test. The results of this study indicate that the population, the Human Development Index, the Construction Cost Index and the GRDP per capita have a positive effect on the DAU, while the area has a negative effect on the DAU. Different test results show that between categories 1 and 3, categories 2 and 3 have different DAU levels. The findings show that non-island regions receive higher DAU allocations than archipelagically characterized areas. The results of category 3 regional GRDP show no influence on DAU allocation.